Review of Miniature Refrigeration System - Gou Zheming; Wei Zhen; Yan Shaohang; Zhu Dongqin; Hou Yu; Liu Xiufang (Zhileng xuebao)
Benefit from the progress of manufacturing technology and the improvement of heat and mass transfer theory, refrigeration systems have been developing towards miniaturization and portability. This paper introduces three kinds of main refrigeration systems: vapor compression refrigeration, semiconductor refrigeration and absorption refrigeration system. Combined with recent literatures at home and abroad, this paper demonstrates the latest developments in miniaturization of systems and core components and then, compares their advantages and disadvantages to suit different occasions. Finally, the paper discusses the bottleneck restricting the miniaturization of refrigeration system, and puts forward the prospect for the future of the miniature refrigeration system.